Assessing English writing of South Indian native Tamil students: The mediocre level requires strategic implications - Bharath M (Journal of Language and Cultural Education)
The study assesses the English writing level of South Indian native Tamil language post-graduate students. The paper highlights the impact of native language sources in English writing and discusses the strategic implications. The study framed an English writing test instrument applying Bloom’s Taxonomy to assess the level of writing. Quantitatively, 300 randomly sampled written transcriptions were taken for analysis. Qualitatively, a structured oneto-one interview was conducted among 27 language instructors, and 127 transcripts were observed to highlight the usage of native language sources, which resulted in poor writing. It assessed the students’ level in L2 writing as mediocre, which was explained by 74% of the sampled responses. It found that the interference of native language in English writing made students make more mistakes in the order of words, subject-verb agreement, usage of tenses, and application of grammar rules. Further, it discussed the strategic implications for improvement as - a) repetitive incremental practice – teaching structures, tenses, and grammar rules of native and target language, b) conversational instruction – sharing differences in native and target languages, sharing of mistakes and errors, and c) timely feedback – a part of follow up mechanism for assessment.